Balancing Benefit and Risk: Continuing Tirzepatide after Allergic Reactions - Beshyah, Salem A. (Ibnosina Journal of Medicine and Biomedical Sciences, 2025)
Tirzepatide is increasingly used for weight management in individuals with obesity. This case report explores the ethical, legal, and clinical considerations involved in continued tirzepatide therapy supported by antihistamine co-treatment after a mild allergic reaction in a patient with severe obesity.A 48-year-old woman with a body mass index of 38 kg/m2 developed a localized erythematous skin reaction at the injection site following dose escalation of tirzepatide, lasting 5 to 6 days after each injection. The reaction persisted despite the use of antihistamines. Motivated by the significant weight loss (12 kg in 6 weeks) and the mild nature of the reaction, a shared decision was made to continue therapy under close monitoring. This was later reconsidered when the benefit of weight loss ceased.This case illustrates a cautious, ethically grounded approach to individualized therapy continuation following mild allergic reactions.
Keywords: obesity; GLP-1 RA therapy; drug allergy; side effects; tirzepatide; ethical practice; medicolegal